Prevalence, risk factors, and survival associated with pulmonary hypertension and heart failure among patients with underlying coronary artery disease: a national prospective, multicenter registry study in China. Issue 15 (5th August 2022) - Huang, Li; Pang, Lingpin; Gu, Qing; Yang, Tao; Li, Wen; Quan, Ruilin; Su, Weiqing; Wu, Weifeng; Tang, Fangming; Zhu, Xiulong; Shen, Jieyan; Sun, Jingzhi; et al.
Abstract: Background: Coronary artery disease (CAD) is the commonest cause of heart failure (HF), whereas pulmonary hypertension (PH) has not been established or reported in this patient population. Therefore, we assessed the prevalence, risk factors, and survival in CAD-associated HF (CAD-HF) complicated with PH. Methods: Symptomatic CAD-HF patients were continuously enrolled in this prospective, multicenter registry study. Echocardiography, coronary arteriography, left and right heart catheterization (RHC), and other baseline clinical data were recorded. Patients were followed up and their survival was recorded. Results: One hundred and eighty-two CAD-HF patients were enrolled, including 142 with HF with a preserved ejection fraction (heart failure with preserved ejection fraction [HFpEF]; left ventricular ejection fraction [LVEF] ≥50%) and 40 with a reduced ejection fraction (heart failure with reduced ejection fraction [HFrEF]; LVEF < 50%). PH was diagnosed with RHC in 77.5% of patients. Patients with PH showed worse hemodynamic parameters and higher mortality. HFrEF-PH patients had worse survival than HFpEF-PH patients. CAD-HF patients with an enlarged left ventricular end-diastolic diameter and reduced hemoglobin were at higher risk of PH. Nitrate treatment reduced the risk of PH. Elevated creatinine and mean pulmonary arterial pressure (mPAP), diastolic pressure gradient (DPG) ≥7 mmHg, and previous myocardial infarction (MI) entailed a higher risk of mortality in CAD-HF patients with PH. Conclusions: PH is common in CAD-HF and worsens the hemodynamics and survival in these patients. Left ventricle enlargement and anemia increase the risk of PH in CAD-HF. Patients may benefit from nitrate medications. Renal impairment, elevated mPAP, DPG ≥7 mmHg, and previous MI are strong predictors of mortality in CAD-HF-PH patients. Trial Registration: ClinicalTrials.gov, NCT02164526.